2015
DOI: 10.1016/j.csl.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Four-participant group conversation: A facilitation robot controlling engagement density as the fourth participant

Abstract: In this paper, we present a framework for facilitation robots that regulate imbalanced engagement density in a four-participant conversation as the forth participant with proper procedures for obtaining initiatives. Four is the special number in multiparty conversations. In three-participant conversations, the minimum unit for multiparty conversations, social imbalance, in which a participant is left behind in the current conversation, sometimes occurs. In such scenarios, a conversational robot has the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…A more detailed investigation into the specifics of how a robot should act to make sure people can participate meaningfully and equally in conversation is described by Matsuyama et al [21]. They used a robot for facilitating a conversation between three participants in which two participants had a strong engagement with each other evidenced by lots of back-and-forth conversation turns, and one of the participants was left out (side-participant).…”
Section: Moderating Interactions and Promoting Inclusivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…A more detailed investigation into the specifics of how a robot should act to make sure people can participate meaningfully and equally in conversation is described by Matsuyama et al [21]. They used a robot for facilitating a conversation between three participants in which two participants had a strong engagement with each other evidenced by lots of back-and-forth conversation turns, and one of the participants was left out (side-participant).…”
Section: Moderating Interactions and Promoting Inclusivenessmentioning
confidence: 99%
“…Most of the studies in social HRI focus on the role of the robot as interactant rather than as assistant to humanhuman social interactions. However, the field has begun to pay more attention to robots being part of and even intervening in social interactions between humans in roles such as group member [20,21], facilitator [22,23], or moderator [24,25]. HRI studies of robots intervening in human-human interactions vary widely in their scope, and are scattered across domains of application, using very different robot designs in a variety of context.…”
Section: Introductionmentioning
confidence: 99%
“…collaboration and engagement) [1,2], in particular, between children [3,4]. In small group play setting, it was observed that children exhibit different levels and types of involvement, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a robot could play the role of a side-participant and support interactions of a participant who is not engaged with others, called "weak engagement" in triadic interactions [2]. In child-child interactions, this weak engagement problem could often be observed since children (6-9 yrs) are still developing social skills at their own pace.…”
Section: Introductionmentioning
confidence: 99%
“…In child-child interactions, this weak engagement problem could often be observed since children (6-9 yrs) are still developing social skills at their own pace. Moreover, children learn social interactions in collaborative play in which "harmonised and unharmonised engagement" [2] can often occur. "harmonised engagement" is defined as the situation where children interact substantially and keep their connections during play.…”
Section: Introductionmentioning
confidence: 99%